PENGARUH PARTISIPASI ANGGARAN TERHADAP SLACK ANGGARAN DENGAN PENEKANAN ANGGARAN DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERATING (SURVEI PADA HOTEL BERBINTANG DI KOTA BOGOR) - Kusuma, Indra Cahya; Hidayat, Hendri (JURNAL AKUNIDA, 2018)
This study aimed to examine the effect of budget participation on slack budgetary with budget emphasisand the uncertainty of the environment as moderating variable on the luxury hotels in the city of Bogor.Designs in this research is quantitative method with the approach of causality or causal. This research isusing purposive sampling method, the number of samples in this study were 48 respondents. Methods ofdata analysis using multiple regression analysis by SPSS 20.0 software program.The results shows thatbudget participation give negative effect and significant on the budget slack and environmental uncertaintymoderating (strengthening) the relationship of participation to the slack budget. while budget emphasis onthe research is not a moderating variable. Simultaneously budget participation, budget emphasis andenvironmental uncertainty had a significant effects on the slack budget.